Obesitas sebagai faktor risiko penurunan aktivitas fisik vs. penurunan aktivitas fisik sebagai faktor risiko obesitas - Burhan, Fatimah Zahra; Susetyowati, Susetyowati; Julia, Madarina (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Obesity as a risk factor for decreased physical activity vs. decreased physical activity as a risk factor for obesityBackground: The worldwide prevalence of obesity keeps increasing. The increase is closely associated with the worldwide increase in physical inactivity. Obesity and inactivity have formed a vicious cycle that is difficult to disentangle, inactivity precedes obesity or the other way around. Objective: This study aimed to assess the association between obesity and physical inactivity in Indonesian population aged 18-65 years. Methods: This was a longitudinal study using the Indonesian Family Life Survey data in 2007 (IFLS 4) and 2014 (IFLS 5). The sample was 16,166 respondents aged 18-65 years who had data on physical activity, age, sex, weight, and height in both IFLS 4 and 5. Results: The prevalence of obesity increased as our subjects became older, from 25.5% in 2007 to 38.9% in 2014. At the same time, the prevalence of sedentary lifestyles increased from 29.8% to 43.0%. Obese individuals had a higher risk of decreasing their activity level, with RR (95%CI) of 1.27 (1.23-1.31), p<0.001. Compared to women, men were less likely to decrease their activity level, RR (95%CI) of 0.91 (0.89-0.94), p<0.001. Individuals with lower education were also less likely to decrease their activity level, RR (95%CI) of 0.94 (0.90-0.98), p<0.001. The decrease in physical activity was a risk factor for obesity observed in later IFLS, OR (95%CI) of 1.21 (1.13-1.29), p<0.001. Conclusions: Obesity was a risk factor for the decrease in physical activity, while the decrease in physical activity was also a risk factor for later obesity. Both conditions indeed formed a vicious cycle